Driving forces of the pervasiveness of street vending: A data article - Al-Jundi, Salem A.; Basahel, Sarah; Alsabban, Abdullah S.; Salam, Mohammad Asif; Bajaba, Saleh (Frontiers in Psychology, 2022)
Street vendors are prominent on public streets and in traditional markets in most developing countries. They raise significant problems for public authorities, residents, pedestrians, and formal retailers. Their informal business is problematic, leading to conflicts and sometimes violence. Moreover, unlicensed street vendors employ children and women and are accused of counterfeiting and drug trading. However, they participate in reducing poverty and unemployment. The current data article aims to formulate a public perception on the problematic issue of street vending pervasiveness by describing a survey dataset on street vending and its main driving factors. Street vending has traditionally be examined by linking it with one or more determinants; thus, the dataset covers poverty, lack of education, immigration, unemployment, urban culture, low-income consumption, resistance, and lack of microfinance as latent constructs. Five measurable variables are introduced that reflect each construct. All variables are measured via seven-point Likert scales. Using a Google Form, 425 responses were collected that reflect the attitudes of the general public in Baghdad, Iraq. Researchers can reuse the dataset (downloadable from the Mendeley Data repository, http://dx.doi.org/10.17632/dh3cv5p7rv.1) to examine the relationships and interconnections among the constructs. This dataset is useful for research on socio-economic problems; more specifically, it introduces reliable measurement models for street vending and the eight factors driving it.